PROSES PENYEMATAN ULOS (MANGULOSI) DALAM PERNIKAHAN ADAT SUKU BATAK TOBA - Sihombing, Sri Ulina; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The Batak Toba are known as a tribe that is very loyal to carry out traditional ceremonies or traditions in various activities from the past. For the Toba people, adat is part of the Batak culture to enhance their quality of life and constitute their cultural identity. The Batak Toba community in Desa Kasikan, Tapung Hulu Kab. Kampar Regency still carries out the Mangulosi Tradition, because according to their belief, this tradition has an influence on family life. This tradition of mangulosi is interpreted as the assistance of love, prayer, warmth and blessing from donations.Therefore in the Batak Toba community is considered as a medium of solidarity in the life of individuals and society. Having ulos itself has an important position in the Batak Toba community order. The purpose of this research is to study the symbolic meaning contained in the mangulosi tradition in the Batak Toba traditional marriage and to find out the changing social system in the mangulosi tradition in the Batak Toba community. The informant selection technique in this study uses a purposive sampling technique. The research method used is descriptive qualitative research method. Theories used are symbolic interaction theory, social system theory and change theory. The results of this study can be concluded that mangulosi is an ancestral tradition carried out in the context of carrying out traditional wedding ceremonies of the Batak Toba community in Kasikan Village, Tapung Hulu District. Keywords: Batak Toba Society, Mangulosi, Traditional Marriage